Re-imagining comics in interactive digital media. - Steven Setiawan Jap. (2011)
This report aims to explore the development of Ember of Rebellion (EoR), a digital graphic novel, developed for my Final Year Project. The project aims to create a possible form of digital graphic novel that preserves the traditional nature of comics while pushing the boundaries into the digital media.